Long-term outcomes of septal reduction for obstructive hypertrophic cardiomyopathy. Issue 1 (July 2015) - Sedehi, Daniel; Finocchiaro, Gherardo; Tibayan, Yen; Chi, Jeffrey; Pavlovic, Aleksandra; Kim, Young M.; Tibayan, Frederick A.; Reitz, Bruce A.; Robbins, Robert C.; Woo, Joseph; Ha, Richard; Lee, David P.; et al.
Abstract Background Surgical myectomy and alcohol septal ablation (ASA) aim to decrease left ventricular outflow tract (LVOT) gradient in hypertrophic cardiomyopathy (HCM). Outcome of myectomy beyond 10 years has rarely been described. We describe 20 years of follow-up of surgical myectomy and 5 years of follow-up for ASA performed for obstructive HCM. Methods We studied 171 patients who underwent myectomy for symptomatic LVOT obstruction between 1972 and 2006. In addition, we studied 52 patients who underwent ASA for the same indication and who declined surgery. Follow-up of New York Heart Association (NYHA) functional class, echocardiographic data, and vital status were obtained from patient records. Mortality rates were compared with expected mortality rates of age- and sex-matched populations. Results Surgical myectomy improved NYHA class (2.74 ± 0.65 to 1.54 ± 0.74, p < 0.001), reduced resting gradient (67.4 ± 43.4 mmHg to 11.2 ± 16.4 mmHg, p < 0.001), and inducible LVOT gradient (98.1 ± 34.7 mmHg to 33.6 ± 34.9 mmHg, p < 0.001). Similarly, ASA improved functional class (2.99 ± 0.35 to 1.5 ± 0.74, p < 0.001), resting gradient (67.1 ± 26.9 mmHg to 23.9 ± 29.4 mmHg, p < 0.001) and provoked gradient (104.4 ± 34.9 mmHg to 35.5 ± 38.6 mmHg, p < 0.001). Survival after myectomy at 5, 10, 15, and 20 years of follow-up was 92.9%, 81.1%, 68.9%, and 47.5%, respectively. Of note, long-term survival after myectomy was lower than for the general population [standardized mortality ratio (SMR) = 1.40, p < 0.005], but still compared favorably with historical data from non-operated HCM patients. Survival after ASA at 2 and 5 years was 97.8% and 94.7%, respectively. Short-term (5 year) survival after ASA (SMR = 0.61, p = 0.48) was comparable to that of the general population. Conclusion Long-term follow-up of septal reduction strategies in obstructive HCM reveals that surgical myectomy and ASA are effective for symptom relief and LVOT gradient reduction and are associated with favorable survival. While overall prognosis for the community HCM population is similar to the general population, the need for surgical myectomy may identify a sub-group with poorer long-term prognosis. We await long-term outcomes of more extensive myectomy approaches adopted in the past 10 years at major institutions.